Revolutionizing Tax Compliance Through Attitudes and Knowledge Worldwide: Merevolusi Kepatuhan Pajak Melalui Sikap dan Pengetahuan di Seluruh Dunia - Shintya Wardani; Sigit Hermawan (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the factors influencing individual taxpayer compliance at the South Sidoarjo Pratama Tax Office in Indonesia. Utilizing data from 75 respondents collected through questionnaires, the research examines the impact of attitudes, subjective norms, behavioral controls, and tax knowledge on compliance. Results indicate that attitudes and tax knowledge significantly influence compliance, while subjective norms and behavioral controls show no significant effect. These findings underscore the importance of fostering positive attitudes and enhancing tax knowledge to improve compliance among individual taxpayers. However, strategies targeting subjective norms and behavioral controls may require further exploration. Policymakers can utilize these insights to tailor interventions aimed at enhancing tax compliance, particularly in local tax offices like the South Sidoarjo Pratama Tax Office. Highlight: Attitudes Drive Compliance: Positive perceptions significantly influence individual taxpayer compliance. Knowledge Enhances Compliance: Understanding tax regulations fosters better compliance. Policy Tailoring for Compliance: Insights aid policymakers in designing effective compliance strategies. Keyword: Tax compliance, Attitudes, Subjective norms, Behavioral controls, Tax knowledge